Congenital diarrhoea in a neonate with hypernatraemia and dehydration - Ammara Kaleem,; Javaria Younus,; Farah Haroon,; Bushra Fatima,; Faria Afzal,; Shumaila Chaudhry, (Journal of the Pakistan Medical Association, 2023)
Diarrhoea, vomiting, and dehydration are frequently encountered in neonatal emergency. However, it is challenging to manage resistant hypernatraemia and metabolic acidosis associated with it. Diagnosing the exact cause is even more difficult. Glucose-galactose malabsorption commonly presents with hypernatraemia and repeated dehydration. In the case described here, the baby started to have diarrhoea in the first week of life and presented in the neonatal emergency with severe dehydration and hypernatraemia. Higher sodium levels were difficult to manage throughout the course of illness. Hypernatraemia and diarrhoea worsened on feeding, whether formula or mother’s feed, which raised suspicion of glucose and galactose malabsorption. So, genetic testing was performed and fructose based formula was started which led to improvement in the condition. Later, genetic testing confirmed our diagnosis. ---Continue